Physical principles of the mossbauer effect for solving inner-nuclear phenomena in solids - AK Shokanov; MF Vereshchak; IA Manakova; YA Smikhan; YA Ospanbekov (Global Journal of Ecology - Peertechz Publications, 2021)
In this work, using a number of examples, it is shown that one of the promising methods for studying the physicochemical state of matter is Mossbauer spectroscopy with all the variety of its methodological approaches. The processes occurring in the shell of atoms have a negligible effect on intranuclear phenomena, and often turn out to be inaccessible for detection by other methods. Mossbauer spectroscopy reveals these influences.  Four methodological approaches have been implemented and an experimental base has been created for observing the resonant absorption of quanta by 57Fe nuclei. Techniques for absorption (MS), Emission Mossbauer Spectroscopy (EMS), Characteristic X-ray Radiation (CXR), Conversion Electron Mossbauer Spectroscopy (CEMS) allow, practically without restrictions on the elemental composition and geometric dimensions of samples (from bulk to nanometer), to carry out studies.